Bruxas na Suécia medieval: arte e tradição na obra de Albertus Pictor (séc. XV) - Sterza, Lorenzo (2023)
The witch, in the western imagination, is an individual that refers to the Middle Ages. From the 15th century, her image was represented in countless contexts, produced in the form of woodcuts, painted on canvas, wood, etc. Therefore, finding that this figure, labelled as something evil and persecuted for centuries by institutions, could find a place within Christian churches, seems a little strange. Strange, until the moment when we realize that the matter is a reality. In this sense, with our dissertation, we present how Albertus Pictor, the most famous painter of churches in Sweden, elaborated, on the walls and vaults of these structures, a series of allegories in which the Witch is the main interpreter of situations that refer to the tasks of the time women. Specifically, we deal with the allegory of the tradition of the Theft of milk, a belief that, over time, was condemned for carrying aspects that were equated with the imaginary of Witchcraft. Therefore, during our investigation, we found out how much the transmission of customs, behaviours, memories, beliefs, legends, which occurred over time among the people of these communities, were elements that influenced Albertus Pictor in the elaboration of his works. Thus, as primary sources of analysis, we used the representations of witches present in the church of Ösmo, in Sweden. Thus, to structure our study, we used a methodology that is based on a qualitative approach that transits through Symbology, present in the representations, using, among others, the theoretical field of the Italian School of History of Religions. Thus, to achieve our intent, with the purpose of analysing the values of artistic works, we used the concepts of Material Culture as well as those of Visual Culture, specifically, those that refer to religion.